Multimodality Imaging Appearance of Intrapericardial Paragangliomas - Palacio, Diana; Gutierrez, Maria del Pilar; Kuyumcu, Gokhan; Rounseville, Benjamin; Shponka, Volodymyr; Betancourt, Sonia (Indian Journal of Radiology and Imaging, 2023)
Paragangliomas are neuroendocrine tumors of the sympathetic and parasympathetic nervous system that originate from neural crest cells. Less than 1% of paragangliomas are found in the heart, originating from intrinsic cardiac ganglia cells in the posterior wall the atria, atrioventricular groove, and along the root of the great vessels. A 10-year review of our institution's database identified nine patients who had documented intrapericardial paragangliomas. We describe the multimodality imaging appearance of these tumors. The most common findings include embedment and wrapping around the great vessels and atrioventricular groove within the confines of the pericardium, markedly avid heterogeneous enhancement, distinct engorged neovascularization, and in large lesions, central low attenuation areas compatible with hemorrhage, necrosis, or cystic degeneration.
Keywords: chest imaging; intrapericardial paragangliomas; multidetector computed tomography